A COHORT STUDY OF POST-GASTRIC-RESECTION GASTRIC-CANCER SURVIVORS AT INCREASED RISK FOR PSORIASIS. - Kumar, Amit; Bharti, Anuja (Student’s Journal of Health Research Africa, 2023)
Objective: The objective of this investigation was to draw a comparison between psoriasis risk factors and incidence between the general population and gastric cancer patients who had undergone gastrectomy. Methods: The hazard ratio (HR) and incidence of onset psoriasis were determined by comparing 140 survivors of gastric cancer for seven years to 300 matched controls from the general population. In gastric cancer survivors, we also estimated the HRs for psoriasis in accordance with obesity, vitamin B12 supplementation, and adjuvant cancer treatment. Results: The gastric cancer group was less likely than the control group to have dyslipidemia. 1.64 percent and 16.62 percent of gastric cancer survivors received chemotherapy and radiotherapy, respectively. Conclusion: In conclusion, gastrectomy-treated gastric cancer survivors had a lower incidence of psoriasis than matched controls. Recommendation: A 4-week break is recommended between courses of potent or very potent corticosteroids. Methotrexate is recommended for the treatment of moderate to severe psoriasis in adults and is less effective than adalimumab and infliximab for cutaneous psoriasis.